New Nitrocellulose-Diethylene Glycol Dinitrate (NC-WITH) Propellant to Support the Development of Munition Independence in Indonesia (Case Study: PT. Pindad) - Nugroho, Vicky Adhityo; Deksino, George Royke; Ruyat, Yayat; Asvial, Muhamad; Gultom, Rudi AG (JTI: Jurnal Teknik Industri, 2024)
PT Pindad, a prominent defense industry leader in Indonesia, is renowned for its high-quality, small-caliber munitions, contributing significantly to the achievements of the Indonesian National Army both nationally and internationally. In the face of globalization and the imperative for robust national defense capabilities, self-sufficiency in munitions production and development is crucial. PT Pindad has been at the forefront of munitions innovation, particularly in addressing challenges related to the supply of propellant materials. This study uses a Feasibility Study approach to explore the innovative use of waste paper as a raw material in producing nitrocellulose (NC) and nitroglycerine (NG). Given NG's sensitivity and volatility, diethylene glycol dinitrate (DEGDN) is proposed as an alternative component in developing an efficient and reliable NC-DEGDN propellant blend. This research supports the strategic goal of advancing Indonesia's munitions independence. Keywords: Defense Industry, Propellant Innovation, Munitions Development, Sustainable Materials